PERAN KETUA KELOMPOK WANITA TANI DALAM PROGRAM PERCEPATAN PENGANEKARAGAMAN KONSUMSI PANGAN DI KECAMATAN IMOGIRI KABUPATEN BANTUL - , CERAH BINTARA NURMAN; , Ir. Roso Witjaksono, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted in Imogiri Sub-district, Bantul Regency, with the aim to know the role of chairwomen of farmer groups in implementation the acceleration and diversification of food consumption program, factors influencing it, and influence of the role of chairwomen of farmer groups for implementation of the program. The basic method in this research was descriptive. The four village samples were chosen purposively. For each village, 15 samples of group members were taken using simple random sampling. The research result indicated that the role of chairwomen of farmer groups in implementation the acceleration and diversification of food consumption program in the high category. The positive influential factor for the role of chairwomen of farmer groups in implementation of the program was attitude of group members in implementation the acceleration and diversification of food consumption program. While, the education level of group members influenced negatively for the role of chairwomen of farmer groups in implementation the acceleration and diversification of food consumption program. The age and motivation of group members did not influence for the role of chairwomen of farmer groups in implementation the acceleration and diversification of food consumption program. The role of chairwomen also did not influence for implementation the acceleration and diversification of food consumption program.